Increase of Deep Intraepithelial Lymphocytes in the Oxyntic Mucosa of Patients With Potential and Overt Autoimmune Gastritis - Lenti, Marco Vincenzo; Vanoli, Alessandro; Miceli, Emanuela; Arpa, Giovanni; Di Stefano, Michele; Soriano, Simone; Capuano, Francesca; Gentile, Antonella; Aronico, Nicola; Coppola, Luigi; Pasini, Alessandra; Luinetti, Ombretta; et al. (Frontiers in Immunology, 2022)
Pathological correlates of potential autoimmune gastritis (AIG), defined by anti-parietal cell antibody (PCA) positivity in the absence of gastric atrophy, have never been described. We herein aimed to assess intraepithelial lymphocyte (IEL) infiltration in gastric corpus of AIG patients. In 2000-2021, among 53 potential AIG patients, we focused on nine (median age 61 years, IQR 53-82; four females) who subsequently developed overt AIG. IEL infiltration of the oxyntic mucosa was assessed before and after developing overt AIG by measuring deep and superficial CD3+ IEL. AIG patients with different degrees of corpus atrophy, healthy controls (HC), active H. pylori gastritis, celiac disease (CD), Hashimoto’s thyroiditis patients were included as controls. Of note, deep, but not superficial, CD3+ IEL count was higher (p<0.001) in potential AIG compared to HC and H. pylori gastritis. Deep CD3+ IEL infiltration did not change before and after the evolution into atrophy (median 9.6, IQR 8.8-12.4, vs 11.3, IQR 9.4-12.9). No difference was found in deep CD3+ IEL infiltration among potential, mild, and severe AIG, and compared to Hashimoto’s thyroiditis or CD. A deep CD3+ IEL cut-off of >7/100 epithelial cells allowed discrimination of any AIG stage and severity (AUC=0.842). We conclude that an increased deep CD3+ IEL infiltration of the oxyntic mucosa could represent a marker of potential AIG. Prospective studies including a larger number of potential AIG patients are needed.